GANGGUAN JIWA DALAM KARYA SENI LUKIS REALIS KONTEMPORER - Novendra, Drs. Erfahmi, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Universitas Negeri Padang, 2017)
The purpose of the creation of this final work is forvisualizing the moral values that containing in the form of mental disorder into the work of contemporary realist painting. The method of creating artwork, using five stages of preparation stage, elaboration stage, synthesis stage, stage of concept realization and completion stage of painting exhibition that has been made. The style used is the Contemporary style is a style where the work follows the modern development or that is called contemporary. Ten works is made representing the theme raised. Talking about Mental Disorders, where the mental disorder becomes a negative view in society, which should be given special attention and appreciated although they have mental disorders.Keyword : Mental Disorders, Painting Arts, Contemporary Realists